The Historical and Political Backdrop to Islamic Studies in Kenya - Mohamed Bakari (International Institute of Islamic Thought, 2014)
This paper argues that the lack of serious attempts to incorporate Islamic studies in Kenya’s academic culture can best be understood by looking at the colonial and postcolonial policies toward university education there. The early missionary influence that shaped the nature of the indigenous educational system had a farreaching impact upon creating a culture of resistance among Muslims toward western education. In the postcolonial period, the new governments tried to create a level playing field for all of their citizens, regardless of religious orientation. But the colonial imapct had already left its mark on Muslims in terms of their visibility at the university level. The Kenyan government did not interfere in what academic programs should be prioritized at this level. But because Christians outnumbered Muslims in academia, their influence created a dearth of indigenous university-generated information and knowledge on Muslim institutions and society. This gap was left to foreign researchers to fill. As a result, Kenya has no indigenous Islamic intellectual culture. If this status quo does not change, Kenyan Muslims will remain vulnerable to foreign Islamist influences.